2020
DOI: 10.4155/fmc-2020-0158
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Repositioning Drugs and Specific Therapeutic Drugs for SARS-CoV-2

Abstract: SARS-CoV-2 has been widely spread around the world and COVID-19 was declared a global pandemic by the World Health Organization. Limited clinically effective antiviral drugs are available now. The development of anti-SARS-CoV-2 drugs has become an urgent work worldwide. At present, potential therapeutic targets and drugs for SARS-CoV-2 are continuously reported, and many repositioning drugs are undergoing extensive clinical research, including remdesivir and chloroquine. On the other hand, structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Although, the importance of antibodies against different viral proteins are still a matter of great concern, and antibodies cross-reactivity against other extremely widespread α- and β-coronavirus, while it is observed that antibody cross-reactivity was found mainly within the β-coronaviridae [ 31 ], predominantly between SARS-CoV-2 and SARS-CoV that showed 90% homology in their amino acid sequence of S1 protein [ 29 ]. At present, few antiviral or immunomodulator agents are available, which include primarily repurposed drugs selected based on their antiviral, antibiotic, anti-inflammatory, or immunomodulatory activities against MERS-CoV, SARS-CoV, human immunodeficiency virus (HIV), and Ebola viruses [ 32 ]. Since the appearance of COVID-19, several drugs, including antivirals (remdesivir, lopinavir, ritonavir, interferon-β, ribavirin), and immunomodulators (chloroquine, hydroxychloroquine, azithromycin, tocilizumab, and ivermectin) have emerged as promising alternatives on an empirical basis with a pharmacological rationale [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although, the importance of antibodies against different viral proteins are still a matter of great concern, and antibodies cross-reactivity against other extremely widespread α- and β-coronavirus, while it is observed that antibody cross-reactivity was found mainly within the β-coronaviridae [ 31 ], predominantly between SARS-CoV-2 and SARS-CoV that showed 90% homology in their amino acid sequence of S1 protein [ 29 ]. At present, few antiviral or immunomodulator agents are available, which include primarily repurposed drugs selected based on their antiviral, antibiotic, anti-inflammatory, or immunomodulatory activities against MERS-CoV, SARS-CoV, human immunodeficiency virus (HIV), and Ebola viruses [ 32 ]. Since the appearance of COVID-19, several drugs, including antivirals (remdesivir, lopinavir, ritonavir, interferon-β, ribavirin), and immunomodulators (chloroquine, hydroxychloroquine, azithromycin, tocilizumab, and ivermectin) have emerged as promising alternatives on an empirical basis with a pharmacological rationale [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…On March, 2020, Jeon et al 52 reported that the replication of SARS-CoV-2 could be prevented by hexachlorophene. As indicated by Liu et al 53 inhibits the replication process at SARS-CoV-2 in Calu-3 lung cells of human by 4-5µM of EC50 56 . Structural knowledge from these relevant proteins could be critical in furthering our understanding SARS-CoV-2 and in discovering as well as developing specific drugs against SARS-CoV-2.…”
Section: Sars-cov-2 Protease Inhibitors (3clpro)mentioning
confidence: 91%
“…It is nevertheless effective against a number of pathogenic viruses, including SARS-CoV and MERS-CoV in vitro and in vivo models 61 . This enzyme was of considerable concern after a treatment of the first COVID-19 and a further regeneration in the U.S 56 . A number of worldwide trials for the efficacy of COVID-19 are currently under way 59 .…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…(75). This enzyme, due to its importance in viral replication and also to the fact that humans are devoid of it, is a very attractive target (76,77). Moreoever due to the availability of its structure with cofactors Nsp7 and Nsp8 (PDB: 6M71) and remdesivir (PDB: 7BV2) the structure based design is feasible.…”
Section: Molecules Docking To Sars-cov2 Enzymesmentioning
confidence: 99%